2004
DOI: 10.1007/s00330-003-2156-5
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen-row multislice computed tomography in the assessment of pulmonary veins prior to ablative treatment: validation vs conventional pulmonary venography and study of reproducibility

Abstract: The aim of this study was to validate multislice computed tomography (MSCT) venography measurements of pulmonary vein (PV) diameters vs conventional pulmonary venography (CPV), and to assess the reproducibility of MSCT data. The study included 21 consecutive patients with atrial fibrillation who were planned for cryothermal ablation of PVs. One day before ablation, all patients underwent CPV and contrast-enhanced non-gated MSCT venography. The MSCT was repeated 3 months after ablation. The CPV images of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Many studies have shown that non-gated MDCT and MR angiography allow accurate assessment of the pulmonary veins, but they ignore the possibility of variation at measuring the size of pulmonary venous ostium during the cardiac cycle [7,[12][13][14][15][16][17][18]. Cronin et al [19] suggested that ECG-gated MDCT improves the quality of 3D images in planning RFCA for atrial fibrillation and becomes more important to delineate the coronary venous anatomy before planning for biventricular pacemaker placement.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that non-gated MDCT and MR angiography allow accurate assessment of the pulmonary veins, but they ignore the possibility of variation at measuring the size of pulmonary venous ostium during the cardiac cycle [7,[12][13][14][15][16][17][18]. Cronin et al [19] suggested that ECG-gated MDCT improves the quality of 3D images in planning RFCA for atrial fibrillation and becomes more important to delineate the coronary venous anatomy before planning for biventricular pacemaker placement.…”
Section: Discussionmentioning
confidence: 99%
“…Transesophageal echocardiography is of limited diagnostic value because it does not always permit a detailed visualization of all PV [1, 2]; conventional angiography has the same limit [2], and it also exposes the patient to ionizing radiation and requires iodine contrast. Multislice computed tomography has recently been introduced in PV imaging with good results [2][3][4]; it has excellent spatial resolution, but on the other hand it also exposes patients to considerable amounts of ionizing radiation [4].…”
Section: Introductionmentioning
confidence: 99%
“…We could not assess whether the use of MRA can reduce procedure times and X-ray exposure, because it would be unethical to carry out a randomized trial where the control group would have to undergo a more invasive or less safe procedure (such as CT angiography or traditional angiography) and would be likely to receive a higher total radiation dose. Recent protocols of multislice CT for PV visualization [2-4] offer excellent images but have an estimated radiation exposure of about 3.1-4.1 mSv [4], a dose that according to current International Commission of Radiological Protection (ICRP) recommendations [29] is likely to cause one fatal radiation-induced cancer every 1,240-1,640 exams (based on an estimated carcinogenic risk of 0.0004 per 1 mSv). Thus, in our opinion, CT only should be used for PV imaging in patients who have absolute contraindications to MRA (e.g., pacemakers or prosthetic heart valves that are not MR-compatible).…”
mentioning
confidence: 99%
“…The most common sustained cardiac arrhythmia is atrial fibrillation (AF) [1] and is present in up to 5% of patients aged 65 years and over [2]. Ectopic electrical activity originating within the pulmonary veins in up to 94% patients has been shown to frequently initiate paroxysms of atrial fibrillation [3] and led to therapies directed at eliminating these foci with radiofrequency catheter ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Neither fluoroscopy nor echocardiography can adequately depict pulmonary venous anatomy [4]. In contrast, multidetector-row computed tomography (MDCT) pulmonary venography is a robust, reliable, and reproducible imaging modality for noninvasive evaluation of pulmonary venous anatomy and ostial diameters [2]. Thin section collimation, allows advanced postprocessing techniques, such as multiplanar reformatting, three-dimensional (3D) volume rendering, and maximum intensity projection (MIP), to be applied for diagnostic evaluation.…”
Section: Introductionmentioning
confidence: 99%